Sustainable Organic Fertilizer Production in Shallots Using Bio-Pulverizer Technology and Solid-State Fermentation for Cost Reduction and Soil Degradation Prevention - Alief Muhammad; Indayani, Sulis Dyah Candra; Dewi, Indah Noor Dwi Kusuma; Iswardani, Kurnia; Andrianata, Mufid; Isyuniandri, Dzaky; Prasetiyo, Dani Hari Tunggal; Achmadin, Wahyu Nur (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
Probolinggo Regency, a key producer of shallots in East Java, faces challenges such as soil degradation, high fertilizer costs, and a decline in harvested land. This community service program aims to address two major issues: inefficiencies in organic fertilizer production and unstable market prices. By introducing a Bio-Pulverizer machine and Solid-State Fermentation (SSF) methods, the program seeks to reduce fermentation time from 30 days to 9 days, improve production efficiency, and reduce pesticide use. The program includes stages of socialization, training, technology implementation, ongoing assistance, and sustainability measures. Key performance indicators include process time reduction, production volume increase, and digital adoption. The program's overall objective is to enhance the sustainability and independence of shallot farming through efficient organic fertilizer production and data-driven decision-making, ultimately contributing to improved soil fertility and farm profitability.